Ścieranie się różnych porządków temporalnych w szkole - doświadczenia nauczycieli = The clash of various temporal orders at school - teachers` experiences - Korzeniecka-Bondar, Alicja (Zielona Góra: Lubuskie Towarzystwo Naukowe)
Based on the analysis of research results concerning everyday teachers?experience of their time at school, it is argued that various temporal rules clash at school, which makes the teacher`s work difficult, if not impossible.As a consequence, the teacher has to deal with constant ambivalence andnumerous dilemmas.
Keywords: kultura szkoły; ścieranie się reguł temporalnych; nauczyciele; codzienność szkolna; school culture; clash of temporal rules; teacher; everydayschool life